Commentary in JNCI (2005)
Importance of Communication Between Producers and Consumers of Publicly Available Experimental Data: Abstract of a commentary by Lance A. Liotta and co-authors in Journal of the National Cancer Institute 2005(Feb 16); 97(4): 310-314. An excerpt: " In an effort to assist others who are perfecting mass spectrometry platforms for profiling, ongoing experimental data were posted for public consumption.